Efektifitas Bimbingan Karir Holland Terhadap Kemandirian Pengambilan Keputusan Pilihan Jurusan Di Perguruan Tinggi Bagi Siswa Kelas XII - Yuliana Nelisma (Jurnal Al-Irsyad: Jurnal Bimbingan Konseling Islam, 2023)
This paper aims to find out whether class XII students at SMAN 2 West Sumatra can independently choose their majors at tertiary institutions thanks to Holland's career guidance. There comes a time in everyone's life when they have to make a choice. share higher-level decision-making processes, such as those related to career or life goals. Every high school student must choose to attend the desired college or continue his education there. It is hoped that students or individuals will be prepared to choose majors in tertiary institutions through Dutch career guidance. This study aims to determine whether class XII students at SMAN 2 West Sumatra benefit from Dutch career guidance in making independent choices about selecting college majors. The author used a pre-experimental study with a pretest-posttest design and one group. Questionnaires or instruments are methods that researchers use to collect data. Data processing with SPSS. In this study, researchers provided respondents with low decision-making independence with traditional Dutch career guidance. This study found that class XII students at SMAN 2 West Sumatra benefited from Holland's career guidance by increasing their independence in making choices. Because the t test (Paired Simple Test) produces a sig result that is smaller than the error, this study rejects Ho and accepts Ha as evidenced by these results. During the data analysis it was also found that on average the independence of the respondents in making decisions regarding their majors increased both during the pre-test and post-test. Thus it can be concluded that Holland's career guidance helps class XII students of SMAN 2 West Sumatra become more independent in making major decisions